Caspofungin versus fluconazole as prophylaxis of invasive fungal infection in high‐risk liver transplantation recipients: A propensity score analysis. Issue 4 (April 2016) - Fortún, Jesús; Muriel, Alfonso; Martín‐Dávila, Pilar; Montejo, Miguel; Len, Oscar; Torre‐Cisneros, Julian; Carratalá, Jordi; Muñoz, Patricia; Fariñas, Carmen; Moreno, Asunción; Fresco, Gema; Goikoetxea, Josune; et al.
Abstract : Targeted prophylaxis has proven to be an efficient strategy in liver transplantation recipients (LTRs). The aim of this study was to compare the effectiveness and safety of caspofungin with that of fluconazole in high‐risk (HR) LTRs. Caspofungin and fluconazole were compared in a multicenter, retrospective, cohort study in HR‐LTRs in Spain. Outcomes were assessed at 180 days after transplantation. A propensity score approach was applied. During the study period (2005‐2012), we analyzed 195 HR‐LTRs from 9 hospitals. By type of prophylaxis, 97 patients received caspofungin and 98 received fluconazole. Of a total of 17 (8.7%) global invasive fungal infections (IFIs), breakthrough IFIs accounted for 11 (5.6%) and invasive aspergillosis (IA) accounted for 6 (3.1%). By univariate analysis, no differences were observed in the prevention of global IFIs. However, caspofungin was associated with a significant reduction in the rate of breakthrough IFIs (2.1% versus 9.2%, P =  0.04). In patients requiring dialysis (n = 62), caspofungin significantly reduced the frequency of breakthrough IFIs ( P  = 0.03). The propensity score analysis confirmed a significant reduction in the frequency of IA in patients receiving caspofungin (absolute risk reduction, 0.06; 95% confidence interval [CI], 0.001‐0.11; P  = 0.044). Linear regression analysis revealed a significant decrease in blood alanine aminotransferase levels and a significant increase in bilirubin levels after administration of caspofungin. Caspofungin and fluconazole have similar efficacy for the prevention of global IFIs in HR‐LTRs in this observational, multicenter cohort study. However, caspofungin was associated with a significant reduction of breakthrough IFIs and, after adjusting for confounders, caspofungin was associated with a lower rate of IA. This benefit is probably more favorable in patients on dialysis. Caspofungin is safe in HR‐LTRs, although bilirubin levels may be increased.